A clinical application study of a stent placement assessment. Issue 47 (25th November 2022) - Yu, Mingsheng; Miao, Xinglu; Huang, Ying; Ma, Lin; Yin, Long; Ren, Hecheng; Wang, Zengguang
Abstract : Background: Atherosclerotic acute carotid occlusion is a specific type of stroke, and controversy exists regarding the surgical strategy, that is, whether an internal carotid artery stent should be placed immediately after opening the occluded vessel. There is no objective evaluation system for this procedure. In a previous study, we summarized an evaluation decision system Emergent Carotid Artery Stent placement decision Evaluation System (ECASES) for emergency stent placement. Study design: This is a prospective, single-center, randomized controlled trial. Patients with acute ischemic stroke caused by atherosclerotic carotid artery occlusion confirmed by imaging (computed tomography/magnetic resonance angiography/digital subtraction angiography) will be randomly divided into the study and control groups, with 101 patients in each group. The study group will undergo surgery according to the ECASES system and the control group will undergo surgery according to the operator's experience. The postoperative outcomes of the 2 groups will be compared. Study outcomes: Primary outcome: Neurological functional status (modified Rankin Scale and National Institutes of Health Stroke Scale scores) of patients 90 days postoperatively. Secondary outcomes: neurological function changes, hemorrhage events, cerebral edema, postoperative modified treatment in cerebral infarction grade, new cerebral infarction, and reocclusion of responsible vessels. Discussion: Currently, no prospective controlled data exist regarding the efficacy and safety of carotid stenting in the acute phase. Previously, we had developed an ECASES stent placement system for acute carotid artery occlusion. The present study will evaluate the efficacy and safety of ECASES in a randomized, double-blind prospective study and clarify its guiding significance in acute atherosclerotic carotid artery occlusion surgery.